High-dose-rate brachytherapy planning in palliative management of hilar cholangiocarcinoma: a case study. Issue 3 (27th April 2015) - Anbumani, Surega; Bilimagga, Ramesh S.; Anchineyen, Pichandi; Jayaraman, Punitha; Palled, Siddanna R.
Abstract Introduction: Cholangiocarcinoma (CCA) or klatskin's tumour involves malignant tumours at the liver hilum's biliary confluence. Incidence of CCA results in unresectable tumours that require appropriate therapy to improve quality of life. The liver is considered as the most frequent site of tumour recurrence. Promising results of long-term survival have been established with computed tomography-guided high-dose-rate brachytherapy. Materials and methods: Intraluminal brachytherapy (ILBT) is performed through the percutaneous transhapatic bile duct drain tube (PTBD). The passage of the brachytherapy guide tube through the bile duct is more complex compared with oesophageal/endobronchial application. Results/discussion: It results in a recoiled view of the tube in the abdominal region of the computed tomography (CT) scan. Owing to inherent artefacts induced by metal stents in CT scans, intersected view is possible between the ILBT guide tube and the intra-hepatic drain tube. It would mislead the planner to track wrong passage that could result in fatal error. Conclusion: In this case study, we contoured the ILBT guide tube by cross-verifying its position with a digitally reconstructed radiograph (DRR) before catheter tracking. Thus, it ensures precise simulation of source dwell positions, thereby avoiding high-dose delivery to nearby vital organs such as intestines, liver hilum and blood vessels.